Receptor‐Level Proximity and Fastening of Ligands Modulates Stem Cell Differentiation. (30th March 2022) - Bae, Gunhyu; Kim, Myeong Soo; Thangam, Ramar; Koo, Thomas Myeongseok; Jang, Woo Young; Yoon, Jinho; Han, Seong‐Beom; Yang, Letao; Kim, Seong Yeol; Kang, Nayeon; Min, Sunhong; Hong, Hyunsik; et al.
Abstract: Cellular adhesion is regulated by the binding of 10 nm sized integrin to Arg‐Gly‐Asp (RGD) ligands present in extracellular matrix proteins. In this study, seed‐mediated growth of gold nanoparticles (AuNPs) on the surface of iron oxide (Fe3 O4 ) nanotemplates is employed to tune the diameter and interdistance of RGD‐bearing AuNPs at the receptor‐level. The Fe3 O4 nanotemplates decorated with RGD‐bearing AuNPs arranged in various RGD diameters and interdistances at the receptor‐levels are flexibly fastened to a substrate. Similar to fully connected RGDs, subreceptor‐level‐gapped (quasiconnected) RGDs activate integrin binding with the adjacent RGDs, which stimulates focal adhesion, mechanosensing, and differentiation of stem cells. This stimulation of stem cells is hindered when the RGD interdistance increases above the receptor‐level gap. However, this stimulation is partially effective when the RGD diameter also increases far above the receptor‐level gap. Strikingly, magnetically attracted fastening of the RGDs toward the substrate via polymer linker tightening fully stimulates adhesion and differentiation of stem cells in a reversible manner, both in vitro and in vivo. Various RGD diameter and interdistance on Fe3 O4 nanotemplates can further elucidate the dynamic receptor‐level RGD proximity‐regulated stem cell differentiation that govern tissue repair. Abstract : Receptor‐level Arg‐Gly‐Asp (RGD) proximity is dynamically modulated. Quasiconnected RGDs and dynamically stabilized RGDs significantly mediates the focal adhesion, mechanotransduction, and differentiation of stem cells compared to unconnected RGDs.